Pizpireto Café: Sustainable Entrepreneurship in Times of Crisis - Ayala, Ricardo Ortiz; Gómez, Graciela Lara; Maldonado, Jesús Hurtado; Nencheva, Violena Hubenova (Archives of Business Research, 2023)
As a result of the economic setback caused by the COVID 19 crisis, many families lost their source of income and were forced to look for alternative forms of income. Thus "PIZPIRETO" Café was born, an example of entrepreneurship in times of crisis, a project that integrates sustainability, one of the life values of its creators. The present paper analyzes the way in which the company shaped and managed sustainability within their business until it became a fundamental pillar to boost the production and commercialization of their coffee, getting involved and being commited with the community of small coffee growers in the state of Veracruz.